Strategi Guru dan Orang Tua dalam Meningkatkan Hafalan Siswa SDIT Al-Ihsan Koto Baru Kabupaten Dharmasraya - Rafqi Amin; Sunimaryanti Sunimaryanti (Journal on Education, 2023)
This study aims to explain the strategies and methods applied by teachers and parents in improving the memorization of SDIT Al-Ihsan Koto Baru students. The method used is descriptive qualitative based on nine indicators of memorization of the Qur'an, namely the strategy of double repetition, not switching to the next verse, memorizing sequentially, using the type of mushof, understanding the meaning of verses, depositing memorization, prioritizing duration, repeating memorization at every prayer time, and faithful to memorization. The results showed that there is a 3T + 1M strategy (Talqin, Tafahhum, Tikrar, and Muraja'ah). Other results are supported by cooperation between teachers and parents in creating good memorization conditions. The driving factors are rote control, tool assistance, electronics. Meanwhile, the inhibiting factor is the indiscipline of parents' time in accompanying children's memorization at home.